Hydrothermal Valorization of Steel Slags—Part I: Coupled H2 Production and CO2 Mineral Sequestration - Crouzet, Camille; Brunet, Fabrice; Montes-Hernandez, German; Recham, Nadir; Findling, Nathaniel; Ferrasse, Jean-Henry; Goffé, Bruno (Frontiers in Energy Research, 2017)
A new process route for the valorization of BOF steel slags combining H2 production and CO2 mineral sequestration is investigated at 300°C (HT) under hydrothermal conditions. A BOF steel slag stored several weeks outdoor on the production site was used as starting material. To serve as a reference, room temperature (RT) carbonation of the same BOF steel slag has been monitored with in situ Raman spectroscopy and by measuring pH and PCO2 on a time-resolved basis. CO2 uptake under RT and HT are, respectively, 243 and 327 kg CO2/t of fresh steel slag, which add up with the 63 kg of atmospheric CO2 per ton already uptaken by the starting steel slag on the storage site. The CO2 gained by the sample at HT is bounded to the carbonation of brownmillerite. H2 yield decreased by about 30% in comparison to the same experiment performed without added CO2, due to sequestration of ferrous iron in a Mg-rich siderite phase. Ferric iron, initially present in brownmillerite, is partitioned between an Fe-rich clay mineral of saponite type and metastable hematite. Saponite is likely stabilized by the presence of Al, whereas hematite may represent a metastable product of brownmillerite carbonation. Mg-rich wüstite is involved in at least two competing reactions, i.e., oxidation into magnetite and carbonation into siderite. Results of both water-slag and water-CO2-slag experiments after 72 h are consistent with a kinetics enhancement of the former reaction when a CO2 partial pressure imposes a pH between 5 and 6. Three possible valorization routes, (1) RT carbonation prior to hydrothermal oxidation, (2) RT carbonation after hydrothermal treatment, and (3) combined HT carbonation and oxidation are discussed in light of the present results and literature data.